Alloys and composites of polybenzoxazines : properties and applications - Rimdusit, Sarawut (Engineering Materials, 2013)
This book provides an introduction to the unique and fascinating properties of alloys and composites from novel commercialized thermosetting resins based on polybenzoxazines. Their outstanding properties such as processability, thermal, mechanical, electrical properties as well as ballistic impact properties of polybenzoxazine alloys and composites make them attractive for various applications in electronic packaging encapsulation, light weight ballistic armour composites and bipolar plate in fuel cells.